Influence of educative game instrument on children's motor development in child day care - Lucie Permana Sari; Sri Sofyani; Bistok Saing; Iskandar Z. Lubis (Paediatrica Indonesiana, 2008)
Background Child day care center is an institution functioning tohelp families to fulfil their child's need by providing stimulation witheducative game instrument (EGI) while they work outside home.Objectives To evaluate motor development of children at child daycare center with EGI stimulation compared with that of childrenwithout stimulation.Methods An experimental study using pretest-posttest control groupdesign was cartied out on children aged 2 to 5 years old, at Islamic CenterDay Care Center (without EGI) and Tanah-Besi Day Care Center inTebing Tinggi (with EGI for six months). Inclusion criteria: healthy,well-nourished children aged 2 to 5 years with informed consent, nodevelopmental delay (confirmed by Denver-II developmental screeningtest). Exclusion criteria: pre term birth children. Forty subjects wereselected by means of simple random sampling. Research data weretaken with Cronbach's motor skills scale. Subjects consisted of 3 to 4years old children, mostly four years old.Results Motor skills scores (mean; SD) of the Islamic CenterDay Care Center group and Tanah-Besi Day Care Center groupbefore stimulation were 104.9; 10.37 and 104.7; 5.47 (P=0.923),respectively, and after stimulation 105.2; 9.56 and 135.3; 7.67 (P<0.001), respectively. Motor skills scores (mean; SD) of Tanah-BesiDay Care Center group before and after stimulation were 104.7; 5.4 7and 135.3; 7.67 (P< 0.001) respectively. Motor skill dimensions score(mean; SD) ofTanah-Besi Day Care Center group before and afterstimulation: speed 28.9; 1.75 and 38.8; 2.79, stability 22.3; 1.02 and30.6; 1.57, accuracy 20.3; 1.15 and 26.7; 1.63, strength 33.3; 1.55and 39.1; 1.68, respectively with P< 0.001.Conclusions There is a significant difference in motor skillsscores and motor skill dimensions of children who receive EGIstimulation compared to those who do not.